Use of Compost in Forestry and Bioagriculture Areas: An Analysis for European Countries - Camargo Mayorga, David Andrés; González Guzmán, Juan Manuel; Jiménez Morales, Pedro (Sociedad y Economía, 2024)
The circular economy aims to minimize waste and reduce environmental impact by deviating from the linear production pattern. It assumes the circular use of materials and products, among which is the use of compost as a biofertilizer in agriculture. With this understanding, the objective of this article is to determine the contribution of compost to areas designated for bioagriculture and the planting of forest species. The aggregated data for 22 European countries were analyzed using the panel data model. The results indicate that the contribution of compost is only marginal for bioagriculture, and for forest species, there is no conclusive evidence of its contribution.